Does verbal encouragement actually improve performance in the 6-minute walk test?. (November 2014) - Marinho, Patrícia E. M.; Raposo, Maria Cristina; Dean, Elizabeth; Guerra, Ricardo O.; Dornelas de Andrade, Arméle
Abstract The purpose of this study was to evaluate the performance in the 6-minute walk test (6 MWT) of elderly patients with chronic obstructive pulmonary disease (COPD) by comparing to a group of healthy elderly patients, performed with and without verbal encouragement. This cross-sectional study compared 40 patients with COPD (forced expiratory volume in the first second (FEV1%) = 53.7 ± 23.8%; forced vital capacity (FVC%) = 65.5 ± 20.8%; and the FEV1/FVC ratio = 55.4 ± 12.4) and 40 healthy elderly patients (control). The 6 MWT's were performed with and without verbal encouragement according to the American Thoracic Society (ATS), monitoring the distance walked (6 MWD), the duration of walking (TW) and the perceived effort index (PEI) through the Borg scale between the groups. No differences were observed in patients with COPD when the tests were performed with and without verbal encouragement for the 6 MWD, TW and PEI, the same occurring in the control group for the 6 MWD, TW and PEI, respectively. The use of verbal encouragement was not sufficient to promote improvement in the performance of the 6 MWT (6 MWD, TW and PEI) of patients with COPD and healthy elderly patients.